A framework for optimal portfolios with sustainable assets and climate scenarios - Ralf Korn (European Actuarial Journal, 2024)
With the increasing impact of global warming and climate change, governments must take actions to reduce CO2output and to encourage more environmentally friendly industrial processes. As the use of climate scenarios is the common method in illustrating possible consequences of the climate changes, we assume that it will also be the basis for political decisions with respect to future sustainability requirements on companies and thus (directly or indirectly) for sustainability constraints for life insurance companies and pension funds. Hence, we assume that bonus/malus measures by the government will already be laid out conditioned on the finally realized climate scenario. We will therefore present a corresponding framework for optimal investment under agreed government measures for the realization of future climate scenarios. This framework is particularly suited for strategies of large institutional investors such as life insurances. It will also be illustrated by explicit examples.
Keywords: 510; Sustainable investment; Large investors; Climate scenarios; Conditional political actions; Portfolio framework